Next generation smart warehouse for ecommerce - Lee, Eric Jun Hong (Nanyang Technological University, 2022)
This project will build a model of a next generation warehouse system an efficient automated storage and retrieval mechanism. The project will examine the state-of-art ASRS systems and design a new automated storage and retrieval system.